Analysis of 100-m backstroke, breaststroke, butterfly and freestyle swimmers at the 2001 European Youth Olympic Days - Arellano, R.; Sanchez-Molina, J. A.; Navarro, F.; de Aymerich, J. (coachesinfo.com, 2002)
INTRODUCTION Analyses of swimming competition have been developed during the last four Olympic Games and International swimming competitions to provide detailed feedback of the performances to coaches and swimmers and analyse the factors influencing swimming performance. While most of these analyses were developed in senior and twice in European Junior Championships, they have never before been developed in international youth competitions. The purpose of our study was to analyse the factors influencing the 100-m races at the 2001 European Youth Olympic Days. METHODS Subjects: 128 swimmers from twenty-six European countries participating in 100-m events (16 finalists by sex and stroke) were analysed during the competition. The male swimmers were 15 or 16 years old and the female swimmers were 13 or 14 years old. Material: Typical set-up for the analysis of swimming competitions was used with 4 video cameras along the swimming pool connected to a video-selector, video-timer and VHS (50 Hz) recorder. Variables: Start time in 15 m (ST), mean swimming velocity (SV), 100-m time, 50-m time, turn-in time in 7,5-m (TI), turn-out time in 7.5-m (TO), total turning time in 15-m (TT), end time in the last 10-m(ET), stroke frequency (SF), stroke length (SL) and stroke index (SI) were measured and compared between sex and strokes. DISCUSSION Male swimmers in comparison to their female counterparts, are faster over each race phase and demonstrate longer SL (+0,15 m) and SI (+0,40), while SF are similar. The differences between the first and second lap times were similar between genders in all strokes. TO were similar between freestyle and backstroke in male and female groups. (Abstract from the World Swimming Science Congress 2002)